Number of pegs influence focal stress distributions and micromotion in glenoid implants: a finite element study - Abdul Wahab, Abdul Hadi (Springer, 2017)
The present study was conducted to compare the stability of four commercially available implants by investigating the focal stress distributions and relative micromotion using finite element analysis. Variations in the numbers of pegs between the implant designs were tested. A load of 750 N was applied at three different glenoid positions (SA: superior–anterior; SP: superior–posterior; C: central) to mimic off-center and central loadings during activities of daily living. Focal stress distributions and relative micromotion were measured using Marc Mentat software. The results demonstrated that by increasing the number of pegs from two to five, the total focal stress volumes exceeding 5 MPa, reflecting the stress critical volume (SCV) as the threshold for occurrence of cement microfractures, decreased from 8.41 to 5.21 % in the SA position and from 9.59 to 6.69 % in the SP position. However, in the C position, this change in peg number increased the SCV from 1.37 to 5.86 %. Meanwhile, micromotion appeared to remain within 19–25 µm irrespective of the number of pegs used. In conclusion, four-peg glenoid implants provide the best configuration because they had lower SCV values compared with lesser-peg implants, preserved more bone stock, and reduced PMMA cement usage compared with five-peg implants.